IMPROVISATION OF STUDENT READING COMPREHENSION THROUGH CLASSROOM ACTION RESEARCH - Moh. Rudiyanto (INTERAKSI : Jurnal Kependidikan, 2018)
This research study aimed to describe implementation of scanning technique to teachreading comprehension. Thisclassroom action research involved 28 students ofIndonesian High school. Data collection techniques used observation andmeasurements. Then, qualitative and descriptive quantitative analysis were used toanalyze the data. The research results showedthat in first cycle, there were 35.71% ofstudents who in poor condition. Then, there were 28.57% of students who were inaverage condition, and also there were only 21.42% of students who were in goodcondition. In addition there were 12.28% students that got excellent condition, and itneed to conduct the second one. The result of the second cycle was that 28.57%students categorized as excellent, 57.14% students was categorized as goodachievement, 7.14% students were categorized as average and poor. It can beconcluded that the improvement of students’ ability on reading comprehensionattaining the expectation.